2013
DOI: 10.1016/j.drugalcdep.2013.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Law enforcement attitudes toward overdose prevention and response

Abstract: Background Law enforcement is often the first to respond to medical emergencies in the community, including overdose. Due to the nature of their job, officers have also witnessed first-hand the changing demographic of drug users and devastating effects on their community associated with the epidemic of nonmedical prescription opioid use in the United States. Despite this seminal role, little data exist on law enforcement attitudes toward overdose prevention and response. Methods We conducted key informant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 47 publications
6
75
0
1
Order By: Relevance
“…Although some studies suggest that policing is moving away from strategies based on aggressive enforcement to more responsive problem-solving frameworks for dealing with the socially marginalized (Green et al, 2013), a broad array of recent laws, ordinances and regulations aimed at America’s growing homeless population suggest this is not necessarily the case (Beckett & Herbert, 2009; Fischer, Turnbull, Poland, & Haydon, 2004; Herbert & Brown, 2006; Mitchell, 2003). In addition to relying on the enforcement of misdemeanor offenses, what some have called “crimes of homelessness,” cities are adopting civility or quality of life ordinances and area restrictions to spatially control their homeless populations (Beckett & Herbert 2008, 2010; McNeil, Cooper, Small and Kerr, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies suggest that policing is moving away from strategies based on aggressive enforcement to more responsive problem-solving frameworks for dealing with the socially marginalized (Green et al, 2013), a broad array of recent laws, ordinances and regulations aimed at America’s growing homeless population suggest this is not necessarily the case (Beckett & Herbert, 2009; Fischer, Turnbull, Poland, & Haydon, 2004; Herbert & Brown, 2006; Mitchell, 2003). In addition to relying on the enforcement of misdemeanor offenses, what some have called “crimes of homelessness,” cities are adopting civility or quality of life ordinances and area restrictions to spatially control their homeless populations (Beckett & Herbert 2008, 2010; McNeil, Cooper, Small and Kerr, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, police in Vancouver have supported the city’s safe injecting facility, as evidenced by greater police referral of public injecting PWID to this site, in part, because of its benefit to the public order (DeBeck et al, 2008). Previous studies have documented shifts in police culture and attitudes towards health of PWID, particularly as a result of the evolving opioid overdose crisis (Green et al, 2013; Wagner et al, 2016). In our study, we found that officers who believed that it was their role to refer PWID to health and social services were significantly more likely to report doing so, suggesting a high degree of self-efficacy to engage in this behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was designed and administered by university researchers and was determined to be exempt from human subjects' regulations by IRB. The survey asked about prior experience with opioid overdose; perceived difficulty administering naloxone; and the importance of having police present at an opioid overdose scene (se Banta- Green et al 2013). To capture attitudes following training we included items from the Opioid Overdose Attitudes Scale (OOAS) developed by 4 Williams et al (2013).…”
Section: Methodsmentioning
confidence: 99%